Kempnyia puri, a new species of Perlidae (Plecoptera) from Rio de Janeiro, Brazil - Da Silva, Fernanda Avelino Capistrano; De-Souza, Marcia Regina; Nessimian, Jorge Luiz (Zootaxa, 2013)
Kempnyia puri sp.nov. is described from male specimens from Rio de Janeiro State, southeastern Brazil. This species is distinguished from its congeners by the male genitalia bearing moderately long and curved hooks with apex directed laterad and a large and rounded dorsal projection of the penial ring.